2016
DOI: 10.1038/srep37733
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of randomness in seismic noise as a short-term precursor to a volcanic eruption

Abstract: Ambient seismic noise is characterized by randomness incurred by the random position and strength of the noise sources as well as the heterogeneous properties of the medium through which it propagates. Here we use ambient noise data recorded prior to the 1996 Gjálp eruption in Iceland in order to show that a reduction of noise randomness can be a clear short-term precursor to volcanic activity. The eruption was preceded on 29 September 1996 by a Mw ~5.6 earthquake that occurred in the caldera rim of the Bárdar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 36 publications
(38 reference statements)
2
36
1
Order By: Relevance
“…This suggests a relationship between the permutation entropy and the spectral content. Such behavior was also evidenced in Glynn and Konstantinou (2016) when the authors linked low values of permutation entropy with the lack of energy at high frequencies. Figure 4c and d are related to the average dominant polarization degree of the events.…”
Section: Characterization Of Long-duration Eventsmentioning
confidence: 72%
See 1 more Smart Citation
“…This suggests a relationship between the permutation entropy and the spectral content. Such behavior was also evidenced in Glynn and Konstantinou (2016) when the authors linked low values of permutation entropy with the lack of energy at high frequencies. Figure 4c and d are related to the average dominant polarization degree of the events.…”
Section: Characterization Of Long-duration Eventsmentioning
confidence: 72%
“…After several tests, we found that different values of n and τ modify the magnitude of the h, but not its temporal evolution (see Additional file 3). We set n = 5 and τ = 1 , as suggested also by Glynn and Konstantinou (2016), because this combination provides high variability between stochastic and deterministic behaviors, being suitable for tracking permutation entropy trends.…”
Section: Permutation Entropymentioning
confidence: 99%
“… SEISMIC. Seismic data have also been successfully analysed using PE [ 41 ], and these time series are a very promising field of research using PE. The data included in this paper was drawn from the Seismic data database, US Geological Survey Earthquake Hazards Program [ 42 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Seismology and economics are emergent fields of PE utilisation. The work in [ 10 ] used noise randomness assessed by PE to quantify its changes as a possible precursor of volcanic activity. An example of PE used in economics is [ 11 ].…”
Section: Introductionmentioning
confidence: 99%